2002
DOI: 10.1021/ic020156v
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Transfer Spectra of Structurally Characterized Mixed-Valence Thiolate-Bridged Cu(I)/Cu(II) Cluster Complexes

Abstract: A series of Cu(II) and Cu(I)/Cu(II) complexes containing the cis-N(amine)(2)S(thiolate)(2) copper complex rac-2 has been synthesized to provide a basis for understanding the charge-transfer spectra of mixed-valence thiolate-bridged Cu(I)/Cu(II) complexes. In combination with Cu(Me(2)-13-N(4)ane), rac-2 yields a monobridged dinuclear homovalent adduct, rac-5, while reaction with CuCl yields the mixed-valance pentanuclear complex rac-6. In the presence of Cu(II)(acac)(2), chiral R,R-1 reacts to form a mixed-vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 50 publications
7
40
0
2
Order By: Relevance
“…Electronic spectra are consistent with the qualitative observations. There are three bands in the vis/ UV spectrum of (bme*daco)Cu: those at 198 nm ( ) 9500 M -1 cm -1 ) and 352 nm ( ) 7000 M -1 cm -1 ) are assigned to L f M charge-transfer bands, consistent with assignments made in the extensive study of Schugar et al 10 A ligand field transition is observed at 504 nm (590 M -1 cm -1 ). In the vis/ UV spectrum of Cu 6 S 4 adam, two bands with much greater molar absorptivity coefficients are observed at 206 nm ( ) 36 000 M -1 cm -1 ) and 454 nm ( ) 6300 M -1 cm -1 ).…”
Section: Copper-copper and Nickel-copper Thiolate Clusterssupporting
confidence: 85%
See 1 more Smart Citation
“…Electronic spectra are consistent with the qualitative observations. There are three bands in the vis/ UV spectrum of (bme*daco)Cu: those at 198 nm ( ) 9500 M -1 cm -1 ) and 352 nm ( ) 7000 M -1 cm -1 ) are assigned to L f M charge-transfer bands, consistent with assignments made in the extensive study of Schugar et al 10 A ligand field transition is observed at 504 nm (590 M -1 cm -1 ). In the vis/ UV spectrum of Cu 6 S 4 adam, two bands with much greater molar absorptivity coefficients are observed at 206 nm ( ) 36 000 M -1 cm -1 ) and 454 nm ( ) 6300 M -1 cm -1 ).…”
Section: Copper-copper and Nickel-copper Thiolate Clusterssupporting
confidence: 85%
“…Herein, we report the synthesis and characterization of adamantane-like M 2 Cu 4 S 4 compounds, which, to our knowledge, are the first of their kind. During the preparation of this manuscript, Schugar and co-workers reported an extensive electronic spectroscopic study of mixed-valent Cu IICu I aggregates with up to five copper atoms based on a related cis-N 2 S 2 ligand whose monomeric Cu II complex building block is shown as structure C. 10 Experimental Section General Techniques. All syntheses and manipulations of materials were carried out under an argon atmosphere using Schlenk techniques or a glovebox.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Charge-transfer spectra in mixed-valence copper(i,ii) species have been examined in some detail. [31,32] Unfortunately, the solid-state UV/visible spec- trum for 2 lacked discrete features, preventing meaningful comparison with previous studies. [31,32] Solid-state measurements were necessary since the compound is insoluble in all common solvents and, moreover, it is not likely that the network structure of 2 is retained in solution.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the coordination of the thiolato groups of [D-1 Cn ] 2¹ to Cu II in these compounds was suggested by the presence of a characteristic near-UV band at around 350 nm and a visible band at around 600 nm in the diffuse reflectance spectra, which are assignable to the S¼Cu II charge transfer and the dd transitions, respectively ( Figure 7). 20 , although they commonly showed positive and negative CD bands from the longer wavelength side in the region of 450850 nm (Figure 8). This observation suggests the difference in the overall molecular topologies between D-2 C3 and D-2…”
Section: Resultsmentioning
confidence: 99%